Factores asociados a la desnutrición o al riesgo de desnutrición en adultos mayores de San Juan de Pasto, Colombia: Un estudio transversal (2017)
ABSTRACT: Malnutrition is a common health problem in older adults; it is related to aging as with other health, social and economic factors. Aim: To establish the frequency of malnutrition or malnutrition risk and associated factors in a sample of older adults located in San Juan de Pasto, Nariño, Colombia. Material and Methods: This was a cross sectional study on a sample of 261 older adults. The Mini Nutritional Assessment (MNA) was used to rate the nutritional status. For cognitive evaluation, the Mini-Mental State Examination (MMSE) was used. Depressive symptoms were evaluated with Yesavage scale and the grade of functional independence with Lawton and Brody scale. A logistic regression model and raw and adjusted odds ratio (OR) with corresponding 95% confidence interval were calculated to establish relation between clinic and sociodemographic factor with MNA. Results: The 60.1% of older adults had malnutrition risk and 6.5% had malnutrition. Older adults who lived in low socioeconomic levels (OR=2,07; IC95%: 1,18-3,64), with functional dependency (OR=2,74; IC95%: 1,07-5,53) and had depressive symptoms (OR=7,02; IC95%: 2,08-23,74) showed a greater malnutrition or malnutrition risk. Conclusions: These findings show a high percentage of older adults with malnutrition or malnutrition risk linked to low socioeconomical levels, functional dependency and depressive symptoms. Integrated management towards the evaluation and planned interventions is required accounting the factors that trigger malnutrition.